2020
DOI: 10.1177/1747021820915107
|View full text |Cite
|
Sign up to set email alerts
|

Strategy mediation in working memory training in younger and older adults

Abstract: Working memory (WM) training with the N-Back task has been argued to improve cognitive capacity and general cognitive abilities (the Capacity Hypothesis of training), although several studies have shown little or no evidence for such improvements beyond tasks that are very similar to the trained task. Laine et al. demonstrated that instructing young adult participants to use a specific visualisation strategy for N-back training resulted in clear, generalised benefits from only 30 min of training (Stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 111 publications
1
21
1
Order By: Relevance
“…In addition to strategy types, we coded the level of detail (LoD) in the open-ended responses (cf. Fellman et al, 2020; Forsberg et al, 2020; Laine et al, 2018; Waris et al, 2021). A detail was defined as either a report of a specific strategy (STR) or of a specific strategy feature (FT).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to strategy types, we coded the level of detail (LoD) in the open-ended responses (cf. Fellman et al, 2020; Forsberg et al, 2020; Laine et al, 2018; Waris et al, 2021). A detail was defined as either a report of a specific strategy (STR) or of a specific strategy feature (FT).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, serial order encoding of verbal or spatial information in WM is not domain general (Ginsburg et al, 2017, Experiments 1, 2, and 3; Zimmermann et al, 2016). More recently, Forsberg et al (2020) showed that instructing WM trainees with visualization strategies can considerably boost WM training performance in the absence of transfer to structurally different transfer tasks (see also Laine et al, 2018).…”
Section: The Facet Model Of Wmmentioning
confidence: 99%
“…Gaining a better understanding of how strategy acquisition impacts patterns of transfer requires a task-analytic training procedure that isolates the cognitive processes that are trained and improved (see also Gathercole et al, 2019;Taatgen et al, 2013). So far, few studies have directly ascertained transfer of training with one particular material to other WM tasks with different materials (e.g., Fellman et al, 2020;Linares et al, 2019). For example, Hilbert et al (2017) systematically varied the stimulus content domains using verbal, numerical, and figural materials for training the two WM functions storage and processing and relational integration.…”
Section: Strategy Use In Working Memory Trainingmentioning
confidence: 99%
“…According to this view, repeated practice with a new and demanding WM task triggers the spontaneous development of a cognitive skill for performing that particular task. Recent evidence on the importance of task-specific strategies and their evolvement during repeated WM practice (Fellman et al, 2020a;Forsberg et al, 2020;Laine et al, 2018;Malinovitch et al, 2020;Waris et al, 2021a, b) supports the skill learning view, as the selection and application of a suitable strategy represent central components of learning a new cognitive skill (Chein & Schneider, 2012). As repeated practice with a limited set of WM tasks only develops skills to perform those specific tasks and their very closely related untrained variants, the challenge is to try to create training protocols that would be less susceptible to this "curse of specificity" that is characteristic of skill learning.…”
Section: Introductionmentioning
confidence: 99%